1989
DOI: 10.1002/ecjc.4430720906
|View full text |Cite
|
Sign up to set email alerts
|

Secret sharing scheme realizing general access structure

Abstract: As a method of sharing a secret, e.g., a secret key, Shamir's (k, n) threshold method is well known. However, Shamir's method has a problem in that general access structures cannot be realized. This paper shows that by providing the trustees with several information data concerning the distributed information of the (k, n) threshold method, any access structure can be realized. the update with the change of the secret trustees and the relation to the threshold graph are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
342
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(343 citation statements)
references
References 3 publications
1
342
0
Order By: Relevance
“…, s |A| at random under the condition that s 1 ⊕· · ·⊕s |A| = s, and give one s i to each participant in A. This scheme was first proposed in [9].…”
Section: Propositionmentioning
confidence: 99%
“…, s |A| at random under the condition that s 1 ⊕· · ·⊕s |A| = s, and give one s i to each participant in A. This scheme was first proposed in [9].…”
Section: Propositionmentioning
confidence: 99%
“…Ito, Saito, and Nishizeki [3] have shown that for any monotone set of subsets, r, there exists a perfect secret sharing scheme for which is the access structure.…”
Section: This Work Performedmentioning
confidence: 99%
“…Replicated secret-sharing [23]. Let Γ ⊆2 [n] be a (monotone) access structure, and let T include all maximal unqualified sets of Γ .…”
Section: Preliminariesmentioning
confidence: 99%
“…A very useful type of "inefficient" secret-sharing scheme is the so-called replicated scheme [23]. 1 The replicated scheme for an access structure Γ proceeds as follows.…”
Section: Introductionmentioning
confidence: 99%